Neglected Students’ Subjective Well-Being in World-Class Universities: A Qualitative Study - Wahyuni, Esa Nur; Efiyanti, Alfiana Yuli; Baharuddin, Baharuddin; Maksum, Ali; Aziz, Rahmat (SCAD Independent, 2024)
Many universities striving for world-class university (WCU) status have increasingly prioritized academic advancement, research, and policy development, often at the expense of students’ subjective well-being. While most studies on the transformation of tertiary institutions into WCUs focus on conceptualization, management challenges, and global impacts, few have considered the well-being of university students. This research aimed to examine the neglect of students’ subjective well-being in universities aspiring to achieve WCU status and to explore the underlying reasons for this oversight. The researchers employed a qualitative approach, collecting data through in-depth interviews with students, lecturers, and university administrators, as well as through observations and document analysis, to investigate the marginalization of students’ well-being. These findings reveal that universities targeting world-class status often overlook students’ well-being in their policies, infrastructure, and institutional culture. The study calls for increased awareness of students’ subjective well-being in the academic community and the provision of structural support for students’ mental health.